1979
DOI: 10.1182/blood.v54.5.1015.bloodjournal5451015
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of factor Xa-factor Va binding sites on the platelets of a patient with a bleeding disorder

Abstract: Factor V (Va) is essential for binding of factor Xa to the surface of platelets. After thrombin treatment, normal platelets release at least five times more factor Va activity than is required for maximal factor Xa binding. The concentration of factor V activity obtained after thrombin stimulation of 10(7) normal platelets is sufficient to allow half-maximal factor Xa binding to 10(8) platelets (10% normal, 90% factor-V deficient). Therefore, factor Va activity is not limiting in platelet-surface factor Xa bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…In addition to the assembly of prothrombinase complex, PPA also includes the assembly of tenase complex, the activation of factor X and the release of intrinsic platelet procoagulant proteins, including the release of platelet factor V. This latter phenomenon is particularly important also for the expression of PPA (Rosing et al, 1991;Miletich et al, 1979;Ahmad et al, 1989;Walsh & Griffin, 1981;Miletich et al, 1978b), since it can express at least 5 times more FVa activity as necessary for maximal factor Xa binding (Ahmad et al, 1989). Platelet factor V is an essential component in maintaining stable and prolonged haemostasis after trauma and also plays a role in early steps of haemostasis (Osterud et al, 1977;Miletich et al, 1978b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the assembly of prothrombinase complex, PPA also includes the assembly of tenase complex, the activation of factor X and the release of intrinsic platelet procoagulant proteins, including the release of platelet factor V. This latter phenomenon is particularly important also for the expression of PPA (Rosing et al, 1991;Miletich et al, 1979;Ahmad et al, 1989;Walsh & Griffin, 1981;Miletich et al, 1978b), since it can express at least 5 times more FVa activity as necessary for maximal factor Xa binding (Ahmad et al, 1989). Platelet factor V is an essential component in maintaining stable and prolonged haemostasis after trauma and also plays a role in early steps of haemostasis (Osterud et al, 1977;Miletich et al, 1978b).…”
Section: Discussionmentioning
confidence: 99%
“…Weiss et al (1979) reported a patient with life-long bleeding diathesis in whom reduced PF3 availability and PCT was observed. The disorder, now referred to as Scott syndrome, has since then been characterized as an isolated deficiency of platelet procoagulant activity (PPA), and reduced prothrombinase activity and MV generation were subsequently demonstrated (Sims et al, 1989;Rosing et al, 1985;Miletich et al, 1979;Ahmad et al, 1989). An additional family displaying the same abnormality has been recently reported (Toti et al, 1996).…”
Section: Patientmentioning
confidence: 99%
See 1 more Smart Citation
“…The only abnormal screening tests were a markedly shortened serum prothrombin time (13 seconds) that was corrected by addition of either platelets or phospholipid, and an impaired platelet PCA activity in PF3a tests using either the recalcification or Russell viper venom assays (see previous section ''Clinical Tests''). 19 A molecular basis for her PCA defect was provided initially by the observations that her platelets developed less prothrombinase activity when stimulated by thrombin, 22 calcium plus thrombin, 23 or the calcium ionophore A23187. 23 Further studies demonstrated that the prothrombinase defect in Scott platelets was due to an impairment in the binding of factor Xa, a defect not corrected by factor Va. 22 Because the latter is a component of the binding site for factor Xa, these findings suggested impaired factor Va binding as the basis for the platelet PCA defect in Scott syndrome.…”
Section: Scott Syndrome: American Patientmentioning
confidence: 99%
“…Scott syndrome, first described by Weiss et al (1979 ), is a rare bleeding disorder associated with an isolated deficiency of platelet procoagulant activity. After activation, these Scott syndrome platelets show decreased exposure of PS ( Rosing et al , 1985 ), impaired capacity to generate plasma membrane vesicles ( Sims et al , 1989 ), and a decreased number of binding sites for factors Va and VIIIa ( Miletich et al , 1979 ; Ahmad et al , 1989 ). In normal platelets the vesicles stemming from the plasma membrane are highly enriched in factor Va‐binding sites ( Sims et al , 1988 ) and are intimately associated with PS exposure and cytoskeleton proteolysis during platelet activation ( Bassé et al , 1994, 1993; Dachary‐Prigent et al , 1995 ).…”
mentioning
confidence: 99%